2004
DOI: 10.2165/00002512-200421070-00005
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Reports of Hypertension Leading to Hospitalisation in Association with Rofecoxib, Celecoxib, Nabumetone and Oxaprozin

Abstract: During early marketing, hospitalisation for acute BP elevation appears to have been reported more frequently for rofecoxib compared with celecoxib. This is consistent with clinical trial data on file with the FDA, and other published studies that found rofecoxib to have a greater effect on BP than other NSAIDs, including celecoxib. This finding may be particularly relevant in older patients given the prevalence of hypertension and cardiovascular disease in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Celecoxib reduced polyp burden in patients with familial adenomatous polyposis by about 30% in a 6-month randomized controlled clinical trial and was approved by the FDA for use in the prevention of colorectal polyps in these patients [10]. While the reduced gastrointestinal toxicity of COX-2-selective inhibitors favors their use, recent findings suggest that certain COX-2 inhibitors, like rofecoxib and possibly valdecoxib, increase the relative risk of cardiovascular morbidity in some persons [11, 12]. …”
Section: Role Of Nsaids and The Chemoprevention Of Crcmentioning
confidence: 99%
“…Celecoxib reduced polyp burden in patients with familial adenomatous polyposis by about 30% in a 6-month randomized controlled clinical trial and was approved by the FDA for use in the prevention of colorectal polyps in these patients [10]. While the reduced gastrointestinal toxicity of COX-2-selective inhibitors favors their use, recent findings suggest that certain COX-2 inhibitors, like rofecoxib and possibly valdecoxib, increase the relative risk of cardiovascular morbidity in some persons [11, 12]. …”
Section: Role Of Nsaids and The Chemoprevention Of Crcmentioning
confidence: 99%
“…Graham and coworkers showed in a nested case-control study that the relative risk for serious coronary heart disease is 1.5 to 3 times higher in patients on rofecoxib versus celecoxib users. Arterial hypertension is more frequently observed in patients taking rofecoxib compared to celecoxib [15][16][17][18]. Finally, although Solomon et al showed that celecoxib increased the incidence of cardiovascular fatalities, the overall mortality was identical with both placebo and celecoxib [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, rofecoxib differs in the following ways: 1) a significantly greater frequency and higher odds of CV events (Mamdani et al, 2004;Solomon et al, 2004a;Graham et al, 2005;Kimmel et al, 2005); 2) a shorter period and a lower dose (even at the clinical dose) leading to the incidence of CV events; and 3) an earlier onset and a greater hypertensive effect correlating closely with CV risk (Brinker et al, 2004;Solomon et al, 2004b;Wolfe et al, 2004;Fredy et al, 2005). Therefore, it is suggested that rofecoxib could have distinctive mechanisms or more potent toxic activity leading to CV risks, in comparison with other selective COX-2 inhibitors or nonselective NSAIDs.…”
Section: Introductionmentioning
confidence: 99%